Penggunaan Metode Action Research pada Persediaan Gudang di Perusahaan Perkebunan Kelapa Sawit - Muhammad Sapruwan (JURNAL CITRA WIDYA EDUKASI, 2017)
PT Karya Makmur Bahagia Gunung Makmur Estate is a company engaged in the palm oil industry. The company is located in Antang Kalang village, Sampit, Central Kalimantan. In November 2003, conducted an examination of the central warehouse inventory assets. From the results of the inventory problems found as follows:1) supplies of goods which are not registered in the list of goods; 2) their physical inventory number is smaller than a note card warehouse; 3) their physical inventory amount is greater than sheds card records; and 4) the physical presence of the card carrying goods warehouse while not physically exist. In this study used methods of action (Action Research). The model used is Stephen Kemmis and Robin Mc Taggart model, ie a model that uses four components of action: Planning, Action, Observing and Reflecting or the famous spiral fashion. Through this model, warehouse inventory problem has been repaired, which cover correcting entry errors, warehousing policy evaluation manjemen in terms of administration, human resources, facilities and infrastructure. Based on the results of the warehouse inventory, subsequently made news event supplies, which will be the basis bleaching warehouse inventory report next position.